Positron emission tomography imaging of long-term expression of the 18 kDa translocator protein after sudden cardiac Arrest in rats - Schroeder, Daniel Carl Horst; Popp, Erik; Rohleder, Cathrin; Vus, Stefanie; Bethencourt, David de la Puente; Finke, Simon R.; Zlatopolskiy, Boris D.; Zischler, Johannes; Drzezga, Alexander; Herff, Holger; Annecke, Thorsten; Hucho, Tim; et al. (Shock, 2021)
Background: - Knowledge about the neuroinflammatory state during months after sudden cardiac arrest is scarce. Neuroinflammation is mediated by cells that express the 18 kDa translocator protein (TSPO). We determined the time course of TSPO-expressing cells in a rat model of sudden cardiac arrest using longitudinal in vivo positron emission tomography (PET) imaging with the TSPO-specific tracer [18F]DAA1106 over a period of 6 months. - Methods: - Five male Sprague Dawley rats were resuscitated from 6 min sudden cardiac arrest due to ventricular fibrillation, three animals served as shams. PET measurements were performed on day 5, 8, 14, 90, and 180 after intervention. Magnetic resonance imaging was performed on day 140. Imaging was preceded by Barnes Maze spatial memory testing on day 3, 13, 90, and 180. Specificity of [18F]DAA1106 binding was confirmed by Iba-1 immunohistochemistry. - Results: - [18F]DAA1106 accumulated bilaterally in the dorsal hippocampus of all sudden cardiac arrest animals on all measured time points. Immunohistochemistry confirmed Iba-1 expressing cells in the hippocampal CA1 region. The number of Iba-1-immunoreactive objects per mm2 was significantly correlated with [18F]DAA1106 uptake. Additionally, two of the five sudden cardiac arrest rats showed bilateral TSPO-expression in the striatum that persisted until day 180. In Barnes Maze, the relative time spent in the target quadrant negatively correlates with dorsal hippocampal [18F]DAA1106 uptake on day 14 and 180. - Conclusions: - After sudden cardiac arrest, TSPO remains expressed over the long-term. Sustainable treatment options for neuroinflammation may be considered to improve cognitive functions after sudden cardiac arrest.